2006
DOI: 10.1021/jf060266a
|View full text |Cite
|
Sign up to set email alerts
|

Heterospectral Two-Dimensional Correlation Spectroscopy of Mid-Infrared and Fourier Self-Deconvolved Near-Infrared Spectra of Sugar Solutions

Abstract: The mid- and near-infrared (mid-IR and NIR) spectra of aqueous solutions of glucose and fructose, fructose and galactose, and glucose and galactose were recorded and analyzed by heterospectral two-dimensional correlation spectroscopy (H2D-CS) to determine characteristic NIR wavelengths for each sugar. Fourier self-deconvolution (FSD) was applied to the NIR spectra prior to H2D-CS analysis to help resolve the strongly overlapping sugar absorptions. Examination of the H2D-CS data gave characteristic absorption w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Figure 3 showed that endothermic peaks for GJW1, GJW2 and RWW were obtained at 270, 269 and 274°C, respectively. In literature, differences between DSC curves of pure tartaric acid and its salt forms were also investigated [6,7]. Results of thermal analyses revealed that salt forms of tartaric acid in waste samples were thermally more stable than the pure tartaric acid.…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
“…Figure 3 showed that endothermic peaks for GJW1, GJW2 and RWW were obtained at 270, 269 and 274°C, respectively. In literature, differences between DSC curves of pure tartaric acid and its salt forms were also investigated [6,7]. Results of thermal analyses revealed that salt forms of tartaric acid in waste samples were thermally more stable than the pure tartaric acid.…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
“…According to Awichi et al, the absorption features at 4300 and 4400 cm −1 are assigned to the combination band of C-H stretch, C-H bending and O-H bending of glucose. Their results suggested that the 4350 cm −1 band may belong to the α-anomer of glucose [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…studied the relationship of the NIR and MIR spectra of water solutions containing glucose and fructose or fructose and galactose. 24 Genkawa et al . reported the detailed development of a dual-wavelength system and demonstrated some examples of application.…”
Section: Introductionmentioning
confidence: 99%